2003
DOI: 10.1177/030802260306600203
|View full text |Cite
|
Sign up to set email alerts
|

Research Priorities in Forensic Occupational Therapy

Abstract: National research priorities have been developed and published by the College of Occupational Therapists (Ilott and White 2001). Such an exercise, however, cannot provide the specific research priorities of a particular area of practice. A questionnaire survey was undertaken to ascertain the specific research priorities of forensic occupational therapists. The survey had three parts: determining research priorities, examining outcome measures and exploring the use of protocol-driven group work. Three specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 8 publications
0
41
0
Order By: Relevance
“…This does not appear to have occurred. The reasons for this cannot be drawn out of the current study, however it suggests that whilst social media platforms do lessen professional isolation and increase communication, this alone is insufficient to change certain behaviours, such as the lack of collaborative research activity within forensic occupational therapy [24]. …”
Section: Discussionmentioning
confidence: 99%
“…This does not appear to have occurred. The reasons for this cannot be drawn out of the current study, however it suggests that whilst social media platforms do lessen professional isolation and increase communication, this alone is insufficient to change certain behaviours, such as the lack of collaborative research activity within forensic occupational therapy [24]. …”
Section: Discussionmentioning
confidence: 99%
“…Participants had clear messages to inform the development of an occupational perspective and occupational therapy in the forensic setting (Duncan et al. , 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Individual goals have to underpin participation in therapy programmes, requiring effective therapeutic relationships. Programmes in the forensic setting tend to be group‐based, with limited appeal (Duncan, Munro & Nicol, 2003; Farnworth et al. ; O’Connell & Farnworth, 2007) and hence this research emphasised occupation in every aspect of participants’ lives, including and beyond group programmes and sustaining a perspective of people as occupational beings (Cronin‐Davis et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large proportion of occupational therapy research originates from the United Kingdom. For example, Duncan et al's () survey of 110 United Kingdom forensic occupational therapists identified research priorities of risk assessment, outcome measurement and intervention effectiveness. Yet, the dearth of assessments and measures specific to forensic occupational therapy continue to hinder effective practice (Duncan et al ., ).…”
Section: Introductionmentioning
confidence: 99%